Structural and spectroscopic properties of Er3+: CdNb2O6 phosphors - (:unkn) unknown (Springer Verlag, 2015)
Rare earth (RE3+) doped luminescence materials are particularly attractive in photonic applications due to their fluorescence arising from 5d→4f or 4f→4f transitions. High purity, compositionally uniform, single phase and uniform particle size powders are required for high resolution and high luminous efficiency in the photonic device developments. Moreover it should be pointed out that the selection of host lattices and active centers for such an optical material is important. So the host lattice of CdNb2O6 may be doped, because it shows thermal and, chemical stability. In this study, we present here the results of a detailed investigation of the spectroscopic properties of the erbium (Er3+) doped cadmium niobate which were successfully prepared by the molten salt technique. It was observed that 0–6 mol % of Er2 O3 addition produced single phase structure in XRD and SEM graphs. (Figs. 23.1 and 23.2). Luminescence spectra of the samples doped with Er3+ ion were conducted in the wavelength-range of 900–1700 nm at 300 K. Fig. 23.3 shows that the concentration quenching occurred in high Er3+ ions doped sample. © Springer Science+Business Media Dordrecht 2015.